Bank Of China : Are You Ready For WTO? - Zhi Lin, Xiang (2005)
The Bank of China (BOC) is one of the "Four Big" state-owned commercial banks in China. This case study is to analyze the external and internal environment of BOC. After analyzing, BOC will realize its advantages and disadvantages, so it can use relevant strategies to compete with other banks.